Impact of the COVID-19 pandemic on Estonian elite athletes: Survey on mental health characteristics, training conditions, competition possibilities, and perception of supportiveness - Parm, U.; Aluoja, A.; Tomingas, T.; Tamm, A.-L. (International Journal of Environmental Research and Public Health, 2021)
Background: The postponement and cancellation of the competition season due to COVID-19 could cause significant mental health problems for an elite athlete. The aim of this study was to describe the mental health characteristics of Estonian elite athletes, their training conditions, competition possibilities, and the support they received during COVID-19. Methods: Athletes completed self-reported questionnaires (including Emotional State Questionnaire). The authors applied descriptive statistics, t-test, and Chi2 test for comparison of study groups (p < 0.05). Results: Altogether 102 athletes (m = 44) were surveyed. The most disturbing issue for athletes was the closing of training centers (57.8%) and cancellation of competitions (50%); 64.7% of athletes reported a negative response from not being able to visit healthcare specialists. Fortunately, athletes could receive virtual coaching. Two-thirds of the athletes had some indication of distress (f > m): 25% of males and 39.7% of females had symptoms indicating depression; f = 27.6%, m = 13.6% anxiety; f = 56.9%, m = 31.8% fatigue (p = 0.021); f = 55.1%, m = 27.2% insomnia (p = 0.009); 27.5% thought about ending their career (frequency in high distress group compared with low: p = 0.022); and 2.9% were certain they would stop their training completely. Family members were the biggest emotional supporters; 16.7% did not get support from anyone. Conclusion: The Estonian sport community needs to adapt to life in a pandemic environment and help athletes to maintain training and competition activities and in turn, their mental health.